PENGARUH PERSEPSI KEADILAN PROSEDURAL DAN PERSEPSI DEPRIVASI RELATIF PADA SISTEM ZONASI TERHADAP MOTIVASI BELAJAR MURID SMP NEGERI DI KOTA BANDUNG - Syilla Eltania Daffa; Ifa Hanifah Misbach; Muhammad Ariez Musthofa (JURNAL PSIKOLOGI INSIGHT, 2021)
AbstractThe zoning system for State Junior High Schools in Bandung is one of the important things related to student learning activities. The zoning system is a school system that can affect the level of student motivation. At the level of student learning motivation can be influenced by internal and external factors, several forms of internal factors, namely in the form of perceptions of the school system and perceptions of deprived conditions. This study aims to determine the influence of procedural justice perception and perceptions of relative deprivation to the motivation of learning student in the zoning system of Public Junior High School in Bandung. The research was conducted with a quantitative approach with a regression model. The research was conducted with a quantitative approach, with a regression model using regression analysis with SPSS 25 software. The sampling technique used was quota sampling to capture 397 respondents according to the research target. The process of distributing the instruments was carried out by distributing questionnaires. The instruments used in this study were the Selection Procedural Justice Scale (SPJS) developed by Severt (2002), the Personal Relative Deprivation Scale (PRDS) developed by Callan et al. (2008), and the scale of learning motivation developed by Aritonang (2008). The data analysis technique used is linear regression and multiple regression to calculate the influence. The results showed that procedural justice perception and perceptions of deprivation relative had a influence on student learning motivation.  AbstrakSistem zonasi SMP Negeri di Kota Bandung merupakan salah satu hal penting terkait aktivitas belajar murid. Sistem zonasi merupakan sistem sekolah yang dapat memengaruhi tingkat motivasi belajar murid. Pada tingkat motivasi belajar murid salah satunya dipengaruhi oleh faktor internal, beberapa bentuk faktor internal yaitu berupa persepsi pada sistem sekolah dan persepsi pada kondisi kesenjangan. Penelitian ini bertujuan untuk mengetahui pengaruh persepsi keadilan prosedural dan persepsi deprivasi relatif terhadap motivasi belajar murid dalam sistem zonasi pada murid SMP Negeri di Kota Bandung. Penelitian dilakukan dengan pendekatan kuantitatif, dengan model regresi yang menggunakan analisis regresi dengan software SPSS 25. Teknik sampling yang digunakan adalah quota sampling untuk menjaring 397 responden yang sesuai dengan target penelitian. Adapun instrumen yang digunakan dalam penelitian ini adalah Selection Procedural Justice Scale (SPJS) yang dikembangkan oleh Severt (2002), Personal Relative Deprivation Scale (PRDS) yang dikembangkan oleh Callan, dkk. (2008), dan skala motivasi belajar yang dikembangkan oleh Aritonang (2008). Hasil penelitian menunjukkan bahwa persepsi keadilan prosedural dan persepsi deprivasi berpengaruh terhadap motivasi belajar murid sebesar.